Management of idiopathic granulomatous mastitis in lactation: case report and review of the literature - Hannah W. Kornfeld; Katrina B. Mitchell (International Breastfeeding Journal, 2021)
Abstract Background Idiopathic Granulomatous Mastitis (IGM) is a benign chronic inflammatory breast condition that mimics two common breast disorders: breast carcinoma and breast abscess. It can form breast masses, fistulae, and fluid collections, resulting in breast disfigurement with retraction and nipple areolar complex (NAC) inversion. IGM most often presents in women of childbearing age within a few years of pregnancy, and can significantly impact lactation. Despite the prevalence of this disease, no current literature describes an approach to managing IGM during breastfeeding. Case presentation A 28-year-old G3P2 patient of Native American origin presented to her obstetrician at 7 months pregnant with worsening left breast swelling and redness. She underwent a mammogram, ultrasound and core needle biopsy that confirmed the diagnosis of Idiopathic Granulomatous Mastitis. During the postpartum period, she underwent intralesional triamcinolone injections of her left breast. Due to the contraindication of breastfeeding after local steroid injection, the patient stopped breastfeeding from the affected breast and continued breastfeeding unilaterally. Conclusions Idiopathic Granulomatous Mastitis is a challenging chronic inflammatory breast disease that affects women primarily in the reproductive years, with a higher incidence in patients of Hispanic, Native American, Middle Eastern, and African descent. Treatment of IGM during pregnancy and lactation has thus far not been addressed. We review the literature on the treatment of IGM in the non-lactating population, and propose considerations for treating breastfeeding women affected by this disease. Traditional treatment has included systemic immunosuppression and surgery, but newer literature demonstrates that intralesional injection of steroid can provide significant symptomatic relief to patients. A diagnosis of IGM does not preclude breastfeeding, though patients may experience challenges with milk production and latch on the affected breast. Individualized care should be provided, with considerations given to the following: side effects of systemic steroids, the need to wean a breast being treated with intralesional steroids, and augmentation of milk production on the unaffected breast to promote continued breastfeeding.